2016
DOI: 10.1016/j.jobcr.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological correlation of Bcl-2 oncoprotein expression in oral precancer and cancer

Abstract: On the basis of the results of our study, we conclude that positive Bcl-2 expression may be an indicator of poor prognosis in oral cancer and precancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
4
8
1
2
Order By: Relevance
“…IHC staining of GI showed positive cytoplasmic expression of Bcl-2 cytoplasmic expression (6.77 %) that was seen to be restricted to the basal and supra-basal layers and negative in the remaining epithelial cell layers. This result is in agreement with that of other investigators (23,24) .This observation might be attributed to that up regulation of Bcl-2 in basal and supra-basal cells serves to maintain the keratinocyte stem cells from apoptosis (25) . Furthermore these results agree with the suggestion of Kummoona et al (2008) (26) , that Bcl-2 plays a role in the control of terminal differentiation of keratinocytes through the protection of basal cells of the proliferative compartment against apoptosis, thus guaranteeing structural epithelial integrity.…”
Section: Discussionsupporting
confidence: 94%
“…IHC staining of GI showed positive cytoplasmic expression of Bcl-2 cytoplasmic expression (6.77 %) that was seen to be restricted to the basal and supra-basal layers and negative in the remaining epithelial cell layers. This result is in agreement with that of other investigators (23,24) .This observation might be attributed to that up regulation of Bcl-2 in basal and supra-basal cells serves to maintain the keratinocyte stem cells from apoptosis (25) . Furthermore these results agree with the suggestion of Kummoona et al (2008) (26) , that Bcl-2 plays a role in the control of terminal differentiation of keratinocytes through the protection of basal cells of the proliferative compartment against apoptosis, thus guaranteeing structural epithelial integrity.…”
Section: Discussionsupporting
confidence: 94%
“…These results were consistent with previous studies that evaluated expression of bcl-2 in oral precancer and dysplasia (8,9,(21)(22)(23)(24)(25) . Nair et al (2011) demonstrated moderate to intense reactivity involving the entire thickness of the epithelium in oral dysplasia (8) .…”
Section: Discussionsupporting
confidence: 93%
“…Nair et al (2011) demonstrated moderate to intense reactivity involving the entire thickness of the epithelium in oral dysplasia (8) . Arya et al (2016) reported positive immunoreactivity in oral precancer lesion involving the basal and parabasal layers (25) . Sadiq et al (2015) confirmed the positive reactivity and revealed statistically significant progressive increase in the count of bcl-2 positive cells from mild, moderate to sever dysplasia (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 geni, ilk kez foliküler lenfoma B hücrelerinde kromozom 18'in karşılıklı translokasyon yeri olarak keşfedilmiştir. 15 Bcl-2, birçok hücre sisteminde apoptozu inhibe eden ilk gendir. 16 Bcl-2 ailesi, anti-apoptotik ve proapoptotik proteinler içermektedir ve apoptozun intrensek yolağının regülasyonundan sorumludurlar.…”
Section: Bcl-2 Proteinleriunclassified
“…Oral kanser vakalarının 11[%36,66, 3 (%10)'ü düşük ekspresyonu ve 7 (%23,33)'si orta derece ekspresyonu ve 1 (%3,33)'i yüksek derece ekspresyonu olmak üzere]'inde ve prekanser vakalarının 14 [%87,50, 8 (%50)'i düşük ekspresyonu ve 6 (%37,50)'sı orta derece ekspresyonu]'ünde Bcl-2 onkoprotein ekspresyonu pozitif belirlenmiştir ve pozitif Bcl-2 ekspresyonunun oral kanser ve prekanserde kötü prognozun bir göstergesi olabileceği sonucuna varılmıştır. 15 Akşit ve Bildik, fibrosarkomda immünohistokimyasal metotla Bcl-2 ve Bax'ın lokalizasyonunu araştırmış ve kontrol dokularına kıyasla tümör dokusunda çok fazla Bax ve Bcl-2 pozitif hücre bulunduğunu saptamışlardır. 5 Cekanova ve ark., Bad molekülünün in vitro meme kanseri hücrelerinin hücre dışı matriks invazyonunu modüle ederek epitelyal-mezenkimal geçişi [epithelial-mesenchymal transition (EMT)] yöneten bazı anahtar molekülleri düzenlediğini ve bunun Bcl-2 protein ailesinin meme kanseri hücreleri üzerine anti-invaziv etkilerinin ilk göstergesi olduğunu belirtmişlerdir.…”
Section: Bcl-2 Proteinleriunclassified